Determinants of Health Behaviors Among University Students: Insights from a Cross-Sectional Study in the Karaganda Region - Karina Yandutkina; Karina Nukeshtayeva; Zhanerke Bolatova; Zhaniya Dauletkaliyeva; Gaukhar Kayupova; Aliya Takuadina; Nurbek Yerdessov; Olzhas Zhamantayev; Gulmira Zhanalina; Nurzhamal Shintayeva; Svetlana Rogova (National Scientific Medical Center, 2024)
Health, a holistic concept encompassing physical, mental, and social well-being, stands as a fundamental value in every individual's life. Despite its paramount importance, many scholars highlight the insufficient commitment to a healthy lifestyle among student populations, often attributed to the challenges associated with academic transitions and social adjustments. Understanding the factors influencing student health behaviors is crucial for promoting well-being and fostering healthy lifestyles. This study employed a cross-sectional, retrospective analysis using primary data. The survey covered socio-economic factors and aspects of a healthy lifestyle among students from various universities in the Karaganda region, including Medical, Technical, and Humanitarian universities. Multiple logistic regression analysis was conducted to identify determinants influencing students' health behaviors. Demographic analysis revealed that surveyed students were primarily urban-born, enrolled in medical university programs, and predominantly lived with parents or relatives. Most students reported financial capacity for medical care and rated their social standing favorably. A significant proportion exhibited a normal BMI, with a notable prevalence of chronic diseases. While emergency care utilization varied, general practitioner visits were common, albeit less frequent among students with chronic conditions. Factors influencing health behaviors included educational program enrollment, socio-economic status, residential circumstances, gender, age, vaccination status. Understanding the complex interplay of factors influencing student health behaviors is essential for designing effective health promotion programs within universities. This study provides valuable insights into the determinants of health behaviors among students, shedding light on areas for intervention and emphasizing the importance of fostering a healthy lifestyle for overall well-being and academic success.